Analisis Efektivitas Strategi Konseling dalam Meningkatkan Keterampilan Komunikasi Interpersonal - NST, Silvi Wulandari; Maibang, Iin Mestika; Hartati Tarigan, Rani; Abdurahman , Abdurahman (Lembaga Intelektual Muda (LIM) Maluku, 2024)
Basically, the implementation of interpersonal communication is a aimed at achieving information exchange, such as life experiences and ideas, as well as fostering cooperative relationships. The purpose of this research is to analyze the effectiveness of interpersonal communication skills on counseling implementation strategies. This study utilizes a qualitative descriptive method, presenting a comprehensive overview of an event. The discussion encompasses the effectiveness of interpersonal communication as a skill necessary for counselors when engaging with clients. The conclusion drawn is that interpersonal communication is highly effective and crucial during counseling sessions